2000
DOI: 10.1161/01.cir.101.4.372
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Homocysteine, Factor VIIa, and Thrombin Generation in Acute Coronary Syndromes

Abstract: Background-It has been suggested by clinical, epidemiological, and experimental in vitro studies that homocysteine potentiates thrombin generation. This prothrombotic effect however has not previously been demonstrated in patients presenting with acute coronary syndromes (ACS). Methods and Results-Patients with ACS (n ϭ117) presenting with confirmed acute myocardial infarction (MI) (n ϭ57) or unstable angina pectoris (UAP) (n ϭ60) were consecutively recruited together with patients (n ϭ18) in whom the presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 29 publications
3
51
1
3
Order By: Relevance
“…In a previous study, 6 we found that high admission plasma homocysteine concentrations were associated with increased thrombin formation, as judged by prothrombin fragments F1+2. Evidence that hyperhomocysteinaemia was triggering the thrombosis cascade was obtained from raised concentrations of activated factor VII (factor VIIa), the product of the reaction of factor VII with tissue factor.…”
Section: Figure 1 C Reactive Protein (Crp) Variations Following (A) Mmentioning
confidence: 71%
“…In a previous study, 6 we found that high admission plasma homocysteine concentrations were associated with increased thrombin formation, as judged by prothrombin fragments F1+2. Evidence that hyperhomocysteinaemia was triggering the thrombosis cascade was obtained from raised concentrations of activated factor VII (factor VIIa), the product of the reaction of factor VII with tissue factor.…”
Section: Figure 1 C Reactive Protein (Crp) Variations Following (A) Mmentioning
confidence: 71%
“…In in vitro models, elevated homocysteine levels induced a hypercoagulable state by reducing thrombomodulin level, protein C activity and heparin sulfate level, as well as inhibiting the binding of tissue plasminogen activators to endothelial cells (10)(11)(12)(13). Hyperhomocysteinemia was associated with activation of coagulation systems in patients with premature atherosclerotic arterial disease and with thrombin generation in patients with acute coronary syndrome (3,4). In hyperhomocysteinemic rabbits, fibrin clots are composed of thinner and more tightly packed fibers compared with normal animals (14).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have associated elevated plasma homocysteine levels to increased risk of cardiovascular diseases such as coronary artery disease (CAD), peripheral artery disease and venous thrombosis (1,2). In patients with acute coronary syndrome, elevated plasma homocysteine levels were associated with hypercoagulability and increased platelet aggregation (3,4). Recent studies have investigated the association of increased homocysteine levels with markers of thrombosis and fibrinolysis in individuals without evidence of CAD and have shown that an increase in homocysteine levels was associated with elevated plasma levels of D-Dimer as well as tissue-type plasminogen activator (t-PA) and plasminogen activator inhibitor (PAI-1) antigen (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…The factors in non-diabetic patients that subsequent events did correlate with were: infarct size (as assessed by troponin [15], previous ACS, insulin resistance [16], plasma homocysteine rose above normal [17] and raised lipoprotein(a) [18]. Of particular interest was the link between raised homocysteins and pro-thrombosis [19].…”
Section: Causative Factors In Patientsmentioning
confidence: 99%